2016
DOI: 10.5223/pghn.2016.19.4.236
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Extraintestinal Manifestations of Crohn Disease in Children

Abstract: PurposeThe aim of this study was to investigate the clinical features and extraintestinal manifestations (EIMs) of Crohn disease (CD) in Korean pediatric patients.MethodsThe medical records of 73 children diagnosed with CD were retrospectively reviewed. Data regarding baseline demographic and clinical characteristics, including CD phenotype at diagnosis based on the Montreal classification, and clinical features and course of EIMs were investigated.ResultsFifty-two (71.2%) of the patients were males. The mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 28 publications
4
22
0
1
Order By: Relevance
“…Korean authors report the case of a 10-year-old girl who presented with vulvitis as the initial symptom; skin biopsy set the diagnosis of MCD [ 19 ]. Anal skin tags have been described in both adult and pediatric CD as flesh-colored, waxy, painless, raised, firm, narrow or broad anal malformations that usually appear in group and may sometimes present granulomatous tissue [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Korean authors report the case of a 10-year-old girl who presented with vulvitis as the initial symptom; skin biopsy set the diagnosis of MCD [ 19 ]. Anal skin tags have been described in both adult and pediatric CD as flesh-colored, waxy, painless, raised, firm, narrow or broad anal malformations that usually appear in group and may sometimes present granulomatous tissue [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Так, в доказательном консенсусе Европейского общества по изучению БК и язвенного колита (ЕССО) имеется указание, что плановая хирургия может быть показана детям при резистентности к консервативному лечению, особенно в препубертатном или пубертатном возрасте, с задержкой роста и при локальном поражении кишечника [55,61]. Экстраполяция рекомендаций для лечения взрослых пациентов не всегда применима у детей, так как есть весомые различия между течением БК во взрослом и детском возрасте, например, дети имеют тенденцию к более тяжелому течению болезни и обширным по протяженности поражениям [44,36,70,71]. В начале 90-х годов Griffiths A.M. и соавт.…”
Section: показания к операцииunclassified
“…In CD, inflammation can occur anywhere in the gastrointestinal tract. CD, although rarely fatal, is refractory and causes abdominal pain, diarrhea, anorexia, and weight loss ( Table 1 ) 3 , 4 , 5) . The clinical presentations of Korean children with CD were similar that observed in Western countries 6 , 7 , 8) .…”
Section: What Is Ibd?mentioning
confidence: 99%
“…This population-based study did not include a national sample; however, it clearly revealed that the incidence of IBD is on the rise in Korean adults. The onset of IBD is reported to be extremely rare in Korean children 1) ; however, recent single-center studies confirmed that the number of pediatric patients newly diagnosed with CD has increased since 2000 3 , 4) . A population-based study in children is essential to accurately determine whether the incidence of IBD is rising continuously in Korea.…”
Section: Is the Incidence Of Ibd Increasing In Korean Adults And Chilmentioning
confidence: 99%
See 1 more Smart Citation